2015
DOI: 10.21014/acta_imeko.v4i1.179
|View full text |Cite
|
Sign up to set email alerts
|

An experimental comparison of complex excitation sequences for eddy current testing

Abstract: Eddy Current Testing (ECT) is a Non Destructive technique widely used in many industrial application fields in which it is very important to detect the presence of thin defects (generally called cracks) in conductive materials. Features of this technique are the cost-effective implementation and the kind of retrieved measured data that make possible to estimate the geometrical characteristics of a crack as position, length, width and depth. The analysis of these characteristics allows the user to accept or dis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2015
2015
2018
2018

Publication Types

Select...
2
1
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 19 publications
0
3
0
Order By: Relevance
“…To this aim information gathered by numerical FEM simulations and previous experimental results [6,12,17] has been taken into account. For the present configuration of the electromagnet and of the GMR sensor, it is found that a small defect produces an image very similar to the spatial profile of a Hermite-Gaussian mode of order (1,1) [34], characterized by 4 main lobes with alternate polarities symmetrically distributed with respect to the defect center [35].…”
Section: Image Processingmentioning
confidence: 99%
See 2 more Smart Citations
“…To this aim information gathered by numerical FEM simulations and previous experimental results [6,12,17] has been taken into account. For the present configuration of the electromagnet and of the GMR sensor, it is found that a small defect produces an image very similar to the spatial profile of a Hermite-Gaussian mode of order (1,1) [34], characterized by 4 main lobes with alternate polarities symmetrically distributed with respect to the defect center [35].…”
Section: Image Processingmentioning
confidence: 99%
“…The former has important representatives in pulsed (PEC) [2][3][4][5] or pseudo-noise excitations [6,7], while the latter proposes signals as the Multi-Frequency (MF-ECT) [8][9][10] and chirp one [11,12]. Pulsed signals are typically analyzed in the time-domain signal processing, while MF-ECT and chirp signals are instead analyzed by the use of transformed domains as the Fourier and the Chirplet.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation